Real-world clinical determinants of alcohol dependence in outpatients with bipolar disorder: a multicenter treatment survey for bipolar disorder in psychiatric outpatient clinics with 2,392 participants - Tokumitsu, Keita; Sugawara, Norio; Adachi, Naoto; Kubota, Yukihisa; Watanabe, Yoichiro; Miki, Kazuhira; Azekawa, Takaharu; Edagawa, Koji; Katsumoto, Eiichi; Hongo, Seiji; Goto, Eiichiro; Ueda, Hitoshi; et al. (Frontiers in Psychiatry, 2024)
BackgroundBipolar disorder is a psychiatric disorder characterized by mood swings between manic and depressed states that causes psychosocial problems. Cognitive function deteriorates with each recurrence, making it important to maintain remission through continued treatment. Bipolar disorder often co-occurs with alcohol dependence, which is known to lead to decreased treatment adherence and increased suicide risk. However, the real-world clinical determinants of alcohol dependence in outpatients with bipolar disorder in Japan remain unclear.MethodsWe conducted an observational study targeting 2392 patients with bipolar disorder using data from the MUSUBI study, a joint project of the Japanese Association of Neuro-Psychiatric Clinics and the Japanese Society of Clinical Neuropsychopharmacology. After determining the prevalence of alcohol dependence and the sociodemographic characteristics of patients with bipolar disorder, multivariate analysis was performed to identify risk factors for alcohol comorbidity.ResultsThe prevalence of alcohol dependence among outpatients with bipolar disorder in this study was 5.7%. The prevalence was 7.6% for males and 3.1% for females. The results of the binomial logistic regression analysis revealed that bipolar I disorder, manic state, comorbidities with other psychiatric disorders, male sex, and suicidal ideation were significantly associated with alcohol dependence. Stratified analysis by gender showed that alcohol dependence was more strongly associated with the presence of suicidal ideation in women than in men.LimitationFirst, because this was an observational study with a cross-sectional design, causal relationships between factors cannot be determined. In addition, this study included outpatients in Japan but lacked information on inpatients. Therefore, it was considered necessary to conduct the study on a larger population in order to generate more robust evidence.ConclusionsWe found that outpatients with bipolar disorder, especially men, had higher rates of alcohol dependence overall than the general population in Japan. In addition, the relationship between alcohol dependence and suicidal ideation was stronger in women than in men with bipolar disorder. There was a strong association between manic states and alcohol dependence in outpatients with bipolar disorder. These results are useful to clinicians because they reinforce real-world clinical evidence for the treatment of bipolar disorder and co-occurring alcohol dependence.